Change in Smoking, Diet, and Walking for Exercise in Blacks - Berg, Carla J. (2012)
Positive changes in one health behavior may be accompanied by other constructive health behavior changes. Thus, the authors investigated the association of smoking reduction and cessation to changes in fruit and vegetable (FV) intake and engaging in walking for exercise. This study included 539 Black light smokers (≤10 cigarettes per day ≥25 days/month) enrolled in a 2 × 2 factorial study (placebo vs. nicotine gum, health education vs. motivational interviewing). Reducing cigarette consumption (p = .02) and quitting smoking (p < .01), as well as receiving the nicotine gum (p = .04), was associated with increased FV intake, after controlling for baseline FV intake. Compared with those who did not reduce their smoking, both reducers (p < .001) and quitters (p < .001) were more likely to walk for exercise at follow-up, after controlling for baseline walking status (p = .01). Thus, addressing one health risk behavior may prompt other positive health behaviors, which may argue for developing interventions targeting multiple health risk behaviors.